Autistic traits and positive psychotic experiences modulate the association of psychopathic tendencies with theory of mind in opposite directions - Steven M. Gillespie (Nature Portfolio, 2017)
Abstract Various clinical disorders, including psychopathy, and autism and schizophrenia spectrum disorders, have been linked with impairments in Theory of Mind (ToM). However, although these conditions can co-occur in the same individual, the effect of their inter-play on ToM abilities has not been investigated. Here we assessed ToM abilities in 55 healthy adults while performing a naturalistic ToM task, requiring participants to watch a short film and judge the actors’ mental states. The results reveal for the first time that autistic traits and positive psychotic experiences interact with psychopathic tendencies in opposite directions to predict ToM performance—the interaction of psychopathic tendencies with autism traits was associated with a decrement in performance, whereas the interaction of psychopathic tendencies and positive psychotic experiences was associated with improved performance. These effects were specific to cognitive rather than affective ToM. These results underscore the importance of the simultaneous assessment of these dimensions within clinical settings. Future research in these clinical populations may benefit by taking into account such individual differences.